ANALISIS POTENSI WISATA BUDAYA DALAM PENGEMBANGAN KEPARIWISATAAN DI DESA PIANTUS KECAMATAN SEJANGKUNG - Sandy Saputra; Sri Buwono; Agus Sugiarto (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the tourism potential of Piantus, the factors inhibiting the development of Piantus tourism, and the efforts to develop Piantus tourism. This research is a qualitative descriptive study. The informants of this research are the community and managers, as well as people from the tourism and culture office. The methods was used in this research is observation, interview, and documentation. The data analysis technique used is an interactive model and to check the validity of the data using triangulation. The results of this study indicate that 1) the potential that exists in this piantus such as a) Bukit Piantus, b) the site and the grave of the datok kullup, c) the sampan bedar competition, d) the ngamping festival, e) handicrafts. 2) factors inhibiting tourism development, namely a) lack of knowledge of the manager or the community, b) incomplete facilities and infrastructure, c) lack of promotion, d) the role of the government has not been maximized, e) high community enthusiasm can lead to inappropriate actions. under control. 3) development efforts to be carried out, namely a) holding annual events, b) websites or social networks, c) installing billboards or directions, d) working with service providers and the government.Keywords: Barriers, Potential piantus, Tourism development efforts.